Peningkatan Kualitas Hidup Pasien Hipertensi dan Diabetes Mellitus Melalui Promosi Kesehatan di UPT Puskesmas Alianyang Kota Pontianak: Improving the Quality of Life of Patients with Hypertension and Diabetes Mellitus through Health Promotion at UPT Puskesmas Alianyang Pontianak City - Nugraha, Fajar; IH, Hariyanto; Kurniawan, Hadi; Najini, Robby (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The number of people with chronic diseases in Indonesia, especially hypertension and diabetes mellitus, continues to increase, including in the Pontianak City area, West Kalimantan. Alianyang Community Health Center, Pontianak City, is one of the basic health facilities that implements the Chronic Disease Management Program. The problem experienced by patients with chronic diseases such as hypertension and diabetes mellitus is a decrease in quality of life due to the disease they suffer. One of the causes of a decrease in a person's quality of life is a lack of knowledge and motivation in implementing a healthy lifestyle. Health promotion in the form of education on healthy lifestyles needs to be provided directly to patients and to prolanist cadres of the Alianyang Health Center. The targets of this activity are patients and prolanist cadres of the Alianyang Health Center. The activity aims to provide information to patients and prolanist cadres regarding efforts to improve the quality of life of hypertension and diabetes mellitus patients. The method used is health promotion through educational videos and leaflets. The results showed that there were changes before and after the delivery of health promotion, namely that the average participant experienced an increase in knowledge between the pre-test and post-test, namely 63.33 and 79.17 respectively. Evaluation of activities through questionnaires showed that participants felt the material presented was very interesting and participants gained new knowledge through the educational media provided.